Modelling the nexus between tertiary learners’ socioeconomic background, social cognitive motivation and achievement-oriented behaviour - Marzia Shurovi; Md Kamrul Hasan; Amine Ounissi (Australian Journal of Applied Linguistics)
While several studies examined the relationship between the achievement motivational beliefs of learners and their English achievement, studies investigating the relationship between social factors and achievement motivational beliefs are scarce. Hence, this research examines the influence of social factors and motivational beliefs on learners’ approach and avoidance motivation. Under a quantitative research design, the data were collected through a questionnaire from 109 tertiary learners from a private university in Dhaka, Bangladesh. The data were analysed using IBM SPSS version 24 and IBM SPSS Amos version 24. The results revealed that the mother’s educational level and school location significantly influenced learners’ self-efficacy which largely impacted their approach motivation. Also, the father’s educational level influenced learners' task value and task value had the largest effect size on learners’ approach motivation. In addition, approach and avoidance motivations were significantly related. Apart from adding new insights into achievement motivation literature, the implications of the findings are also discussed.